Development of Edutainment Flashcard Media to Improve IPAS Learning Outcomes - Anis Nurfitriya; Fitria Dwi Prasetyaningtyas (Jurnal Penelitian Pendidikan IPA, 2025)
This type of research is a Research and Development study that produces a product and tests its effectiveness with the Borg and Gall method. The purpose of this study was to develop edutainment flashcard media to determine its effectiveness in helping improve the learning outcomes of Getasbawlong Class IV SDN Kendal. Flashcards are media that contain images and writing in the form of Cards. While Edutainment is the incorporation of games in learning. A total of 24 fourth grade students were used as research subjects. The results showed that flashcard edutainment media is feasible to use in learning, with validation of 82% and 85% of media experts and material experts with very feasible criteria. The results of the N-Gain effectiveness test showed a value of 0.59 which was included in the medium criteria. It can be concluded that edutainment flashcard media proved effective in improving learning outcomes, seen from the increase in the average value of pre-test to post-test of 25.11. Thus, the existence of flashcard edutainment media has a positive effect on student learning outcomes, therefore the media is suitable for use in learning practices.